Skip main navigation
We use cookies to give you a better experience, if that’s ok you can close this message and carry on browsing. For more info read our cookies policy.
We use cookies to give you a better experience. Carry on browsing if you're happy with this, or read our cookies policy for more information.
Roof structure

Recursive Functions on Lists

Computing with lists

  • There are two approaches to working with lists:

    • Write functions to do what you want, using recursive definitions that traverse the list structure.
    • Write combinations of the standard list processing functions.
  • The second approach is preferred, but the standard list processing functions do need to be defined, and those definitions use the first approach (recursive definitions).
  • We’ll cover both methods.

Recursion on lists

  • A list is built from the empty list and the function . In Haskell, the function is actually written as the operator , in other words : is pronounced as cons.
  • Every list must be either
    • or
    • for some (the head of the list) and (the tail)

where is pronounced as

  • The recursive definition follows the structure of the data:
    • Base case of the recursion is .
    • Recursion (or induction) case is .

Some examples of recursion on lists

Recursive definition of length

The length of a list can be computed recursively as follows:

length :: [a] -> Int
length [] = 0                  # the base case
length (x:xs) = 1 + length xs  # recursion case

Recursive definition of filter

  • filter is given a predicate (a function that gives a Boolean result) and a list, and returns a list of the elements that satisfy the predicate.
filter :: (a->Bool) -> [a] -> [a]

Filtering is useful for the “generate and test” programming paradigm.

filter (<5) [3,9,2,12,6,4] -- > [3,2,4]

The library definition for filter is shown below. This relies on guards, which we will investigate properly next week.

filter :: (a -> Bool) -> [a] -> [a]
filter pred []    = []
filter pred (x:xs)
  | pred x         = x : filter pred xs
  | otherwise      = filter pred xs

Computations over lists

  • Many computatations that would be for/while loops in an imperative language are naturally expressed as list computations in a functional language.
  • There are some common cases:

    • Perform a computation on each element of a list:
    • Iterate over a list, from left to right:
    • Iterate over a list, from right to left:
  • It’s good practice to use these three functions when applicable
  • And there are some related functions that we’ll see later

Function composition

  • We can express a large computation by “chaining together” a sequence of functions that perform smaller computations
  1. Start with an argument of type
  2. Apply a function to it, getting an intermediate result of type
  3. Then apply a function to the intermediate result, getting the final result of type
  • The entire computation (first , then ) is written as .
  • This is traditional mathematical notation; just remember that in , the functions are used in right to left order.
  • Haskell uses . as the function composition operator

    (.) :: (b->c) -> (a->b) -> a -> c
    (f . g) x = f (g x)

Performing an operation on every element of a list: map

  • map applies a function to every element of a list

    map f [x0,x1,x2] -- > [f x0, f x1, f x2]

Composition of maps

  • map is one of the most commonly used tools in your functional toolkit
  • A common style is to define a set of simple computations using map, and to compose them.

    map f (map g xs) = map (f . g) xs

This theorem is frequently used, in both directions.

Recursive definition of map

map :: (a -> b) -> [a] -> [b]
map _ []     = []
map f (x:xs) = f x : map f xs

Folding a list (reduction)

  • An iteration over a list to produce a singleton value is called a fold
  • There are several variations: folding from the left, folding from the right, several variations having to do with “initialisation”, and some more advanced variations.
  • Folds may look tricky at first, but they are extremely powerful, and they are used a lot! And they aren’t actually very complicated.

Left fold: foldl

  • foldl is fold from the left
  • Think of it as an iteration across a list, going left to right.
  • A typical application is
  • The is an initial value
  • The argument is a list of values which we combine systematically using the supplied function
  • A useful intuition: think of the argument as an “accumulator”.
  • The function takes the current value of the accumulator and a list element, and gives the new value of the accumulator.

    foldl :: (b->a->b) -> b -> [a] -> b

Examples of foldl with function notation

Examples of foldl with infix notation

In this example, + denotes an arbitrary operator for f; it isn’t supposed to mean specifically addition.

foldl (+) z []          -- > z
foldl (+) z [x0]        -- > z + x0
foldl (+) z [x0,x1]     -- > (z + x0) + x1
foldl (+) z [x0,x1,x2]  -- > ((z + x0) + x1) + x2

Recursive definition of foldl

foldl        :: (b -> a -> b) -> b -> [a] -> b
foldl f z0 xs0 = lgo z0 xs0
                lgo z []     =  z
                lgo z (x:xs) = lgo (f z x) xs

Right fold: foldr

  • Similar to , but it works from right to left
foldr :: (a -> b -> b) -> b -> [a] -> b

Examples of foldr with function notation

Examples of foldr with operator notation

foldr (+) z []          -- > z
foldr (+) z [x0]        -- > x0 + z
foldr (+) z [x0,x1]     -- > x0 + (x1 + z)
foldr (+) z [x0,x1,x2]  -- > x0 + (x1 + (x2 + z))

Recursive definition of foldr

foldr            :: (a -> b -> b) -> b -> [a] -> b
foldr k z = go
            go []     = z
            go (y:ys) = y `k` go ys

Relationship between foldr and list structure

We have seen that a list [x0,x1,x2] can also be written as

    x0 :  x1 : x2 : []

Folding (:) over a list using the empty list [] as accumulator gives:

foldr (:)  [] [x0,x1,x2]
  -- >
  x0 :  x1 : x2 : []

This is identical to constructing the list using (:) and [] ! We can formalise this relationship as follows:

Some applications of folds

sum xs = foldr (+) 0 xs
product xs = foldr (*) 1 xs

We can actually “factor out” the that appears at the right of each side of the equation, and write:

sum      = foldr (+) 0
product  = foldr (*) 1

(This is sometimes called “point free” style because you’re programming solely with the functions; the data isn’t mentioned directly.)

Share this article:

This article is from the free online course:

Functional Programming in Haskell: Supercharge Your Coding

University of Glasgow

Get a taste of this course

Find out what this course is like by previewing some of the course steps before you join:

  • Haskell history poster
    Brief History of Haskell

    What are the origins of the Haskell programming language? In this article, Dr Jeremy Singer explores the history of Haskell.

Contact FutureLearn for Support